THE HYGIENIC CONDITIONS OF PRESCHOOL KINDERGARTENS - Imamova Akida Obidjon qizi; Khobiljonova Shakhnoza Rustam qizi (Innovate Conferences, 2025)
The hygienic conditions of preschool kindergartens play a crucial role in the health and well-being of children, particularly those who are frequently ill. This study investigates the relationship between hygiene practices in preschool settings and the incidence of illnesses among attending children. Through a comprehensive literature review and analysis of existing studies, we identified key hygienic factors influencing the frequency of respiratory and other common infections in young children. Our findings underscore the importance of stringent hygiene protocols, including regular handwashing, proper sanitation, and effective illness management policies, in reducing the spread of infectious diseases in preschool environments.
Keywords: preschool hygiene, frequent illnesses, child health, infection control, kindergarten sanitation